Analysis of Agenda Monitoring System Governance with the COBIT 2019 Framework in the DSS01 Domain - Abdurrahman Harits; Salsha Sabilla Nurhidayat; Ririn Aryanti; Mufidah Karimah; Heri Haerudin (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
An agenda monitoring system plays a strategic role in supporting the effectiveness of leadership performance, particularly ensuring that every organizational activity is managed in a structured and measurable manner. For this system to operate optimally, a comprehensive evaluation of its management and implementation mechanisms is required in accordance with applicable information technology governance standards. This study used the Capability Level Assessment methodology, with the primary objective of measuring process capability levels based on five subdomains within DSS01, namely DSS01.01 to DSS01.05. Data collection was conducted through questionnaires distributed to staff using the system. The data was then analyzed quantitatively to obtain CLI (Capability Level Indicator) values ​​as a benchmark for achievement. The analysis showed that three subdomains—DSS01.01, DSS01.02, and DSS01.03—had reached capability level 4, with DSS01.01 even approaching level 5. However, the other two subdomains—DSS01.04 and DSS01.05—remained at level 3, indicating a gap between the established capability targets. The study's conclusions confirm that the system has generally performed well, but still requires improvement, particularly in incident and problem management. Recommendations include developing standard operating procedures (SOPs), implementing a ticketing system, training human resources, and conducting regular evaluations. The implementation of COBIT 2019 has proven effective in providing guidance for evaluating and improving IT governance, particularly in the government sector.